2005
DOI: 10.2214/ajr.184.1.01840121
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MRI of Bladder Cancer: Evaluation of Staging Accuracy

Abstract: MRI shows good reproducibility between reviewers for staging bladder cancer. Although overall staging accuracy was only moderate, the accuracy for differentiating superficial versus invasive disease and organ-confined versus non-organ-confined disease was high.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
1
10

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(154 citation statements)
references
References 28 publications
3
140
1
10
Order By: Relevance
“…38 According to Tekes et al, gadolinium-enhanced MRI has an accuracy of 85% in differentiating noninvasive versus invasive disease and was 82% accurate in differentiating organ-confined from nonorgan-confined disease. 39 Overstaging can be a problem with MRI, however, because of acute edema and hyperemia after recent biopsy or resection, as both may give the appearance of tumor spread. 38 Continued advances in MRI may help to further improve staging in the future.…”
Section: Cystoscopymentioning
confidence: 99%
“…38 According to Tekes et al, gadolinium-enhanced MRI has an accuracy of 85% in differentiating noninvasive versus invasive disease and was 82% accurate in differentiating organ-confined from nonorgan-confined disease. 39 Overstaging can be a problem with MRI, however, because of acute edema and hyperemia after recent biopsy or resection, as both may give the appearance of tumor spread. 38 Continued advances in MRI may help to further improve staging in the future.…”
Section: Cystoscopymentioning
confidence: 99%
“…DCE-MRI has been shown to significantly improve tissue characterization, and both the dynamic parameters of the contrast enhancement (e.g., onset time, rate of enhancement, etc.) and the pharmacokinetic modeling parameters have been used to differentiate between cancer and normal tissue in the breast (5), bladder (6), and bone (7). DCE-MRI has been quite successful in diagnosing and staging prostate cancer in the peripheral zone (PZ) (8 -12); however, there appears to be some overlap in the enhancement patterns between the tumor and the transitional zone (10).…”
mentioning
confidence: 99%
“…It improved up to 66% when differentiating between NMIBT and MIBT ( Table 2). Tekes et al [13] reported overstaging as the most common error in 32% with an overall accuracy at 62%. Their results also improved, up to 85%, when differentiating between NMIBT and MIBT.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Tekes et al [13] evaluating the ability of MRI in staging bladder tumors without DWI, but with enhanced and unenhanced sequences, the agreement among reviewers was good (kappa = 0.80) and accuracy in differentiating between invasive and non-invasive was 82% -85%. Takeuchi et al [14] used dynamic contrast sequences along with T2W and DWI, and reported an accuracy of 88% for T2W plus DWI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation